Artificial Evolution 11th International Conference, Evolution Artificielle, EA 2013, Bordeaux, France, October 21-23, 2013. Revised Selected Papers - Legrand, Pierrick; Corsini, Marc-Michel; Hao, Jin-Kao; Monmarché, Nicolas; Lutton, Evelyne; Schoenauer, Marc (Theoretical Computer Science and General Issues, 2014)
This book constitutes the refereed proceedings of the 11th International Conference on Artificial Evolution, EA 2013, held in Bordeaux, France, in October 2013. The 20 revised papers  were carefully reviewed and selected from 39 submissions. The papers are focused to theory, ant colony optimization, applications, combinatorial and discrete optimization, memetic algorithms, genetic programming, interactive evolution, parallel evolutionary algorithms, and swarm intelligence.